THE INFLUENCE OF GENERATION Z CONSUMER BEHAVIOR ON PURCHASE MOTIVATION IN E-COMMERCE SHOPPE - Frans Sudirjo; Luckhy Natalia Anastasye Lotte; I Nyoman Tri Sutaguna; Andriya Risdwiyanto; Muhammad Yusuf (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The study aims to investigate the impact of generation Z consumer behavior on site qualities, privacy security, online shopping services, and shopping enjoyment, as well as mediating shopping pleasure on online impulse purchases. The rapid expansion of e-commerce, along with the buying habits of Generation Z, leads to unexpected or impulse purchases. This study is quantitative, with primary data collected through a purposive sampling method. The number of respondents who met the criterion of generation Z in West Java, aged 18-35 years, and had shopped on the West Java Shoppe website was 159. The data analysis method employs the Structural Equation Model (SEM) in conjunction with the SmartPLS 3.0 programs. The findings reveal that site features have a direct impact on online impulse purchase behavior, but not privacy security. Online shopping services have little direct impact on online impulse purchases. Site qualities, privacy security, and online buying services all have an impact on purchasing experience. Shopping pleasure increases online impulse buying behavior.